ENHANCING INNOVATION ROLES OF PESANTREN BUSINESS INCUBATOR IN PONDOK PESANTREN SUNAN DRAJAT - Ahwarumi, Biyati; Sawarjuwono, Tjiptohadi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2017)
Business Incubator is one of PPSD’s (Pondok Pesantren Sunan Drajat) sub-units that supports their owneconomy independency. PPSD have existed as an important part of education, social and especially economic institution for Muslim community in East Java. Each year, Muslim intellectuals graduate from PPDS as Santri graduates, and mostly work, not only as religion teachers, but also as entrepreneurs, back in their hometown. The phenomenon of Santri Entrepreneurs appears to be the main inspiration for Business Incubator foundation. The researcher subsequently observes such phenomenon, also known as Santri anti-poverty agent, by using Action Research method as a base of observation for data collecting, analysis and synthesis process. The aim is to describe innovative methods of PPSD’s Business Incubator in generating entrepreneurs along with pesantren ecosystem where this research was conducted. The research findings are the description of knowledge management and recommendation for developing entrepreneurship within incubator related to PPSD policy.